Single- and Double-Coordination Mechanism in Ethylene Tri- and Tetramerization with Cr/PNP Catalysts - Britovsek,GJP; McGuinness,DS; Wierenga,TS; Young,CT (ACS Catalysis, 2015)
The mechanism of ethylene trimerization and tetramerization with a chromium–diphosphinoamine (Cr–PNP) catalyst system has been studied with combined experimental and theoretical methods. Of the total product output, 1-octene, cyclopentanes, n-alkanes, and higher (C10+) olefins are formed with a fractional (∼1.4) order response to ethylene concentration, whereas 1-hexene formation is approximately first-order in ethylene. Theoretical studies suggest a mechanism involving a cationic monometallic catalyst in Cr(I) and Cr(III) formal oxidation states. A key feature of the developed model is the occurrence of a double-coordination mechanism in which a bis(ethylene) chromacyclopentane intermediate is responsible for 1-octene formation as well as the other coproducts that have a greater than first-order response to ethylene. In contrast, 1-hexene is formed primarily from a mono(ethylene) chromacyclopentane intermediate. The selectivity of catalysis is governed by the competition between single- and double-coordination pathways. The mechanistic model developed displays excellent correlation with experimental observations and is able to fully explain the formation of all products generated with this catalyst.